Identification of MicroRNAs Regulating Clostridium perfringens Type C Infection in the Spleen of Diarrheic Piglets - Pengfei Wang; Qiaoli Yang; Zunqiang Yan; Xiaoyu Huang; Xiaoli Gao; Shuangbao Gun (Current Issues in Molecular Biology, 2023)
Clostridium perfringens (C. perfringens) type C is one of the common bacteria in piglet diarrhea, which seriously affects the swine industry’s development. The spleen plays crucial roles in the resistance and elimination of pathogenic microorganisms, and miRNAs play important roles in regulating piglet diarrhea caused by pathogens. However, the mechanism by which miRNAs in the spleen are involved in regulating C. perfringens type C causing diarrhea in piglets remains unclear. The expression profiles of the spleen miRNAs of 7-day-old piglets challenged by C. perfringens type C were studied using small RNA-sequencing in control (SC), susceptible (SS), and resistant (SR) groups. Eight-eight differentially expressed miRNAs were screened. The KEGG pathway analysis of target genes revealed that the miRNAs were involved in the MAPK, p53, and ECM–receptor interaction signaling pathways. NFATC4 was determined to be a direct target of miR-532-3p and miR-133b using a dual-luciferase reporter assay. Thus, miR-133b and miR-532-3p targeted to NFATC4 were likely involved to piglet resistance to C. perfringens type C. This paper provides the valuable resources to deeply understand the genetic basis of C. perfringens type C resistance in piglets and a solid foundation to identify novel markers of C. perfringens type C resistance.